Investigating the relationship between self-compassion and body image with postpartum depression in women referring to health centres in Iran - Azam Bakhteh; Nader Salari; Nasrin Jaberghaderi; Tahereh Khosrorad (Wolters Kluwer Medknow Publications, 2023)
Background: Depression is the most important postpartum mental disorder that can lead to irreversible damage to family health if not addressed, including inability to provide maternal care, impaired mother-child relationship, impaired growth, and development of the child, to marital problems, and sometimes the risk of suicide and infant death. The aim of this study was to investigate the relationship between self-compassion and body image with postpartum depression. Material and Method: In this study, 150 pregnant women in the third trimester and 6 weeks postpartum completed the Short Form Self-Compassion Questionnaire (SCS-SF), Multidimensional Self-Body Relationships (MBSRQ), and Edinburgh Postpartum Depression Inventory (EPDS). Depending on the type of study, descriptive statistics such as mean, median, and standard deviation were calculated for quantitative, frequency, and relative frequency variables. Kolmogorov-Smirnov test was used to evaluate the normality of the distribution of scores in each questionnaire. Data were analyzed using parametric proportional statistical tests (paired t-test, Pearson correlation, and linear regression) at the level of significance less than 0.05. Results: Based on the findings, the relationship between self-compassion and postpartum depression was not significant. Self-kindness had a significant positive relationship, and self-judgement had a significant negative relationship with depression (p < 0.01). Body image had a significant predictive effect on postpartum depression (p < 0.05). Conclusions: Negative body image as a risk factor for postpartum depression should be considered by healthcare providers and used in the prevention and treatment of postpartum depression.